Sebaran Total Suspended Solid (Tss) Di Kawasan Muara Sungai Kampar Kabupaten Pelalawan Provinsi Riau - Purba, Ranto Haposan; Mubarak, Mubarak; Ghalib, Musrifin (Jurnal Perikanan dan Kelautan, 2018)
The study was conducted from January to February 2017 in Kampar River Estuary Area of Pelalawan District of Riau Province. Water sample analysis was done at the Chemical Oceanography Laboratory of the Faculty of Fisheries and Marine. This study aims to determine the distribution of TSS (total suspended solid) at high tide and low tide. The method used is survey method and determination of station point using pur-posive sampling. The results showed that the total suspended solid (TSS) distribution during tidal to low tide with the average value of the lowest TSS content at station 2 was 91 mg/l and the highest was in station 7 of 670 mg/l. At low tide, the average val-ue of the lowest TSS content at station 1 is 65 mg/l and the highest is at station 6 of 448 mg/l.